The sufficiency of current training curricullum for different industries and adequacy of the minimum academic requirement for safety and health officer - Zainuddin, Sabri (2006)
Occupational Safety and Health Act (OSHA) 1994 considers a competent Safety and Health Officer (SHO) to be at least those with a minimum of a pass in the Sijil Pelajaran Malaysia, attended SHO course and passed the SHO examination, and have a minimum of three years working experience in the field of occupational safety and health (OSH). Having such a requirement for competency to help manage OSH program in a diverse, demanding and high risk work environments appears highly inadequate. A study was carried out to address the question of sufficiency of a single SHO curriculum to meet the demand of a diverse and high risk work environment, and the question of adequacy of current academic qualifications to meet the duties of SHO as prescribed by OSHA. This study was based on questionnaires and perceptions of 32 SHOs towards both questions. The statistical parameters that were analysed includes the Analysis of Variance (ANOVA) and Pearson Correlation and the descriptive tests of frequencies and percentages. Findings from the statistical analysis on the perceptions of the respondents on the two issues above indicated that the single SHO course curriculmn is sufficient to prepare SHO for the different industries, and the minimum qualification of SPM with three years of working expereince in OSH is adequate for the SHO to carry out his or her responsibilities as specified in the SHO Regulations